From Bat to Worse: The Pivotal Role of Bats for Viral Zoonosis - Harald Brüssow (Microbial Biotechnology)
ABSTRACT Zoonotic infections are increasingly observed and bats (Chiroptera) are playing a pivotal role here. The causal chain of events has been elucidated for Henipavirus (family: paramyxoviruses) infections. Deforestation combined with climate change has reduced the food sources of Pteropus fruit bats and attracted them to fruit trees planted around piggeries in Malaysia, transmitting Nipah virus to pigs as amplifying hosts and then to pig farmers and abattoir workers. Similar scenarios were seen in Australia where Pteropus bats transmitted Hendra virus to horses as intermediate hosts for human infections. Pteropus bats contaminated palm sap collected in Bangladesh with Nipah virus where fatal human‐to‐human transmissions occurred annually. Less direct evidence links coronaviruses carried by Rhinolophus bats with SARS and COVID‐19 pandemics and a piglet epidemic in China. Rousettus bats living in caves transmitted the Marburg virus (family: filovirus) to miners in Africa. Most cases of human rabies in North America were caused by bat lyssaviruses (family: Rhabdoviruses). Bats are viral reservoir species for various virus families (reovirus, Hepacivirus of Flavivirus family, influenza A viruses). Bats are the only flying mammals which opened enormous evolutionary possibilities resulting in a worldwide radiation with 1400 species. Some bat species are represented by huge populations that come together in extremely crowded resting places that are conducive to viral transmission. Bats have evolved mechanisms that tolerate virus replication but suppress the associated pathology, making them healthy carriers for many viruses. It is speculated that with that strategy bats avoid an arms race with viruses for resistance and anti‐resistance mechanisms. The excretion of viruses that are highly pathogenic for other mammalian orders could be used as biological weapons to defend their habitat against intrusion by mammalian competitors, including humans. This hypothesis might explain the increasing involvement of bat viruses in emerging infectious diseases observed in recent decades and expected in the future.